2015
DOI: 10.1039/c4nr05551a
|View full text |Cite
|
Sign up to set email alerts
|

Origin of electrochemical activity in nano-Li2MnO3; stabilization via a ‘point defect scaffold’

Abstract: Molecular dynamics (MD) simulations of the charging of Li2MnO3 reveal that the reason nanocrystalline-Li2MnO3 is electrochemically active, in contrast to the parent bulk-Li2MnO3, is because in the nanomaterial the tunnels, in which the Li ions reside, are held apart by Mn ions, which act as a pseudo 'point defect scaffold'. The Li ions are then able to diffuse, via a vacancy driven mechanism, throughout the nanomaterial in all spatial dimensions while the 'Mn defect scaffold' maintains the structural integrity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…The Mg ions acted as "point defect pillars" and held the Li + diffusion pathways open and clear for smoother ion movement, which lead to enhanced capacity, better cycling performance and preserved the structural integrity. This observed "point defect pillars" type of mechanism is not unique as it was formally proposed by Sayle et al [50] in lithium manganese oxide (Li 2 MnO 3 ) cathode materials. Interestingly, improvements in both the rate capability and initial discharge capacity were observed by He et al [51] in their study of Al-Ti-oxide coated LiCoO 2 as can be shown in Table 1.…”
Section: Improved Electrochemical Performancementioning
confidence: 50%
“…The Mg ions acted as "point defect pillars" and held the Li + diffusion pathways open and clear for smoother ion movement, which lead to enhanced capacity, better cycling performance and preserved the structural integrity. This observed "point defect pillars" type of mechanism is not unique as it was formally proposed by Sayle et al [50] in lithium manganese oxide (Li 2 MnO 3 ) cathode materials. Interestingly, improvements in both the rate capability and initial discharge capacity were observed by He et al [51] in their study of Al-Ti-oxide coated LiCoO 2 as can be shown in Table 1.…”
Section: Improved Electrochemical Performancementioning
confidence: 50%
“…Li + exchange by H + , which possibly originates from the decomposition reaction of an aprotic electrolyte solution, was proposed based on the data collected at 55°C. 19 Such electrolyte decomposition at an elevated temperature for pure Li 2 MnO 3 was further supported by gas analysis at different temperatures. 16 Nevertheless, oxygen loss is the dominative process for the pure Li 2 MnO 3 sample at 25°C.…”
Section: Mno 3 -Based System With Partial Anionic Redox and Holementioning
confidence: 90%
“…Hence, in this study, a mixture of such phases coexists in the high-temperature amorphous phase and leads to the formation of a heterostructure during the recrystallization of the nanoparticle, which is retained on annealing to 0 K. On the contrary, a similar high-temperature simulation study of a parent Li 2 MnO 3 tends to yield nanoparticles without spinel components, because the layered Li 2 MnO 3 phase is maintained from low to high temperatures. 33 Related composites or heterostructures were previously synthesized by simulations for binary MnO 2 35,44 and TiO 2 32,45…”
Section: ■ Discussionmentioning
confidence: 99%
“…39 This approach was previously carried out successfully for the simulated synthesis of Li 2 MnO 3 nanoparticles. 33 Lithium Intercalation. Lithium atoms were introduced into the spinel nanoparticle; specifically, four models were generated: Li 1.25 Mn 2 O 4 , Li 1.5 Mn 2 O 4 , Li 1.75 Mn 2 O 4 , and Li 2.0 Mn 2 O 4 .…”
Section: ■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation